Human Development Index (HDI) As a Planning Plan For Dealing Globalization of Asean Economic Society (MEA) in Indonesia - Ade Manggala Hardianto; Bambang Tjahjadi; I Made Narsa (International Consortium of Education and Culture Research Studies, 2017)
The purpose of this study is to map the human development index (HDI) of each region and regional planning efforts against the economic community of ASEAN (MEA). The research data used is secondary data sourced from the Central Bureau of Statistics (BPS) from 2010 until 2016. The research methodology used is comparative research using secondary data analysis method, depicting human development index as measured by society welfare, that is health, education, and life standard or often called economic. The research results show that there are 9 provinces that have different HDI with Jakarta Capital City as the capital of Indonesia, West Nusa Tenggara (NTB), East Nusa Tenggara (NTT), West Kalimantan (KALBAR), North Kalimantan, Gorontalo, West Sulawesi , North Maluku and West Papua and Papua. The impact of this study is that central government focuses more on areas with different Human Development Index (HDI) with DKI Jakarta and equitable development to improve infrastructure in the area.